Design of a conceptual bed mattress for reducing pressure on bony prominences - Salman, Ozlem (2016)
Elderly care emphasizes the social and personal requirements of older people who need assistance with daily activities and health care, where almost always the main caregiver is the other element of the couple (husband or wife). In the context of Wellbeing, and from its perspective, it is important to have information regarding the type of care needed by bedridden elderly people.. Regardless of the needs, they desire independence and autonomy in their life so they need better, more efficient and integrated systems for health and social care. Nowadays, there is an increase on the availability of assisted devices that can be used at home, decreasing the constant requirement for health professional assistance. The main objective of this study is to propose a conceptual solution consisting on the development of a bed mattress in order to reduce pressure points and protect fragile elders. Also, it intends to show a solution that may reduce the number of caregivers to only one. Besides it allows a safety design structure, to be able to take care of older people with disabilities in order to live independently and be active in their home.